The global financial crisis and the resulting change in the Mauritian investment pattern. (2015) - Fauzel, Nazreen B.; Fauzel, Sheereen
The housing bubble in the USA that started in August 2007 has had a cascading effect on many other global stock markets due to the extent and severity of the crisis. Although being a much smaller and less open marketplace, the Stock Exchange of Mauritius (SEM) has also resented the waves of the crisis. Hence, the objective of this study is twofold, where firstly, the level of contagion of the SEM resulting from the US stock market crisis was tested and secondly the resulting spill over effects defined by a change in the investment pattern of investors were studied in the Mauritian economy. The correlation coefficient between SEMDEX and Volatility Index (VIX) in the crisis period increased significantly explaining the evidence of the contagion effect. More so, based on the survey implemented and the data analysed thereof, there was a loss of trust among Mauritian investors in the SEM.